Extractive Metallurgy Division - Reaction of Pure Tantalum with Air, Nitrogen, and Oxygen - W. M. Albrecht; W. D. Klopp; B. G. Koehl; R. I. Jaffee (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1962)
Kinetic studies were made of the reactions of tantalum with oxygen, nitrogen, and air at 400o to 1500°C. The tantalum-oxygen reaction is linear from 500° to 1250°C. The tantalum-nitrogen reaction follows a cubic rate law at 400° to 700°C and a parabolic rate law at 800" to 1475°C. The reaction behavior in air is initially parabolic followed by a transition to linear behavior. In the search for high-temperature materials, considerable interest is being shown in the refractory metal, tantalum. It is the third highest melting metal with a melting point of 2996°C. Also, tantalum has excellent ductility, making it one of the most workable refractory metals. In considering high-temperature applications of tantalum, the oxidation kinetics of the metal must be known. Such information also serves as a basis for the development of corrosion resistant tantalum-base alloys. Therefore, this study was made to investigate the reaction of tantalum with air, nitrogen, and oxygen. LITERATURE Several oxides of tantalum have been reported. The pentoxide, Taz05, is the only oxide of tantalum whose identity has been established. A high-temperature modification, aTa2Os, has been reported by several investigators.1-4 A low-temperature phase, ßTa2O5, undergoes an allotropic transformation at 1320o to 1350oC. 5-8 Four other oxides of tantalum have been reported. The oxides TaO2, TaO, and Ta4O have been reported by schonberg.9 A suboxide Ta2O, was observed by Wasilewski 6. However, the presence of oxides lower than Ta2O5 is questioned by Lagergren and Magneli.7 In oxidation studies, vermilyeal0 and Peterson, et al.,12 reported one possible phase intermediate between Ta and Ta2O5. Only Ta2O5 was formed in the tantalum air reaction, as reported by Michae1.l3 Several studies have been made on the kinetics of the tantalum-oxygen reaction. vermilyeal4 investigated the range 50° to 300°C and found that the rate of growth of a thin adherent oxide film could be described by the Cabrera-Mott theory. Gulbransen and Andrew15,18 studied the reaction kinetics of tantalum in oxygen pressure of 1/10 atm at 250° to 450°C. At all temperatures the reaction followed the parabolic rate law for periods up to two hours. The oxidation behavior in the range 500" to 1000°C was found to be linear at oxygen pressures of 0.2 to 600 psi according to Peterson. et al.l1 At very low pressures (1 x 10-3 to 2 X lo-' mm of Hg) Gebhardt and seghezzi17 reported linear oxidation at 800° to 1500°C. The reaction of tantalum with air is similar to the reaction with oxygen. Studies have been made by Waber, et a1.,12 and Michae1.l3 Two nitrides of tantalum, TaN and Ta2N are known. Their structures have been determined by Brauer and Zapp 18,19 The tantalum-nitrogen reaction kinetics have been investigated by Gulbransen and Andrews. 15, 16 The reaction follows the parabolic rate law at 500° to 850°C at a nitrogen pressure of 1/10 ,atm. At the same temperature, the tantalum-nitrogen reaction is much slower than the tantalum-oxygen reaction. EXPERIMENTAL TECHNIQUES Material— The material used in this study was high-purity, electron-beam-melted tantalum obtained from the Temescal Metallurgical Corp. The hardness of the as received ingot was 76 Vhn. The analysis of the material is given in Table I. Methods—Cylindrical specimens of tantalum approximately 0.9 cm in diam and 0.5 cm in length